Factors Influencing Grade 12 ABM Students to Vandalize Bestlink College of the Philippines’s Premises (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Vandalism in schools has become a critical educational and social problem. It is particularly serious at the high school level. Vandalism is the defacement and/or destruction of property, such as drawing graffiti and unnecessary illustrations and damaging the furniture of the school. Every institution should maintain cleanliness and good ambiance within its vicinity. In that case, every school should strictly implement the rules about vandalism because its presence makes the school facilities less attractive and even unusable. The researchers used a descriptive research design, survey method, and quota sampling to gather necessary information. The respondents of this study were 50 selected grade 12 Accountancy, Business, and Management (ABM)students from sections 12-10 to 12-18 with the class schedule of Tuesday, Thursday, and Saturday. Based on the results, the factors influencing Grade 12 ABM students to vandalize Bestlink College of the Philippines’s premises are the following: (1) peer pressure (it is one of the factors why many students vandal inside the school because young people are more easily affected to imitate their peers; they tend to follow their bad behavior to prove that they are independent and can do almost anything), (2) behavior (it has a great influence regarding the issue of school vandalism because most of them do not have discipline; as a result, they tend to write anywhere, such as in walls and other school properties), (3) freedom of expression ( the students want to freely express themselves because no one can listen to their thoughts and rants; hence, they tend to write their thoughts in walls and draw on their armchairs to express their feelings), and (4) lack of awareness against vandalism (lack of informative guidelines such as the Republic Act about bullying and destroying school property serve as one of the problems encountered by the students with regard to vandalizing because they do not know the consequences of this action). The students should have the self-discipline to maintain the good ambiance of the school. The strict implementation of the rules and regulations about the vandalism is also necessary. Each individual should take part in educating others about the consequences of school vandalism. Additional study on how to lessen vandalism within the school premises is also important. Students should also realize the values of discipline and should respect the work of others.
Keywords: factor, vandalism, school property